SN 2016coi/ASASSN-16fp: an example of residual helium in a typeIc supernova?. Issue 3 (11th May 2018) - Prentice, S J; Ashall, C; Mazzali, P A; Zhang, J-J; James, P A; Wang, X-F; Vinkó, J; Percival, S; Short, L; Piascik, A; Huang, F; Mo, J; et al.
ABSTRACT: The optical observations of Ic-4 supernova (SN) 2016coi/ASASSN-16fp, from ∼2 to ∼450 d after explosion, are presented along with analysis of its physical properties. The SN shows the broad lines associated with SNe Ic-3/4 but with a key difference. The early spectra display a strong absorption feature at ∼5400 Å which is not seen in other SNe Ic-3/4 at this epoch. This feature has been attributed to He i in the literature. Spectral modelling of the SN in the early photospheric phase suggests the presence of residual He in a C/O dominated shell. However, the behaviour of the He i lines is unusual when compared with He-rich SNe, showing relatively low velocities and weakening rather than strengthening over time. The SN is found to rise to peak ∼16 d after core-collapse reaching a bolometric luminosity of L p ∼3 × 10 42 erg s −1 . Spectral models, including the nebular epoch, show that the SN ejected 2.5–4 M⊙ of material, with ∼1.5 M⊙ below 5000 km s −1, and with a kinetic energy of (4.5–7) × 10 51 erg. The explosion synthesized ∼0.14 M⊙ of 56 Ni. There are significant uncertainties in E ( B − V )host and the distance, however, which will affect L p and M Ni . SN 2016coi exploded in a host similar to the Large Magellanic Cloud (LMC) and away from star-forming regions. The properties of the SN and the host-galaxy suggest that the progenitor had M ZAMS of 23–28 M⊙ and was stripped almost entirely down to its C/O core at explosion.